(p+3)(p-7)=0

Simple and best practice solution for (p+3)(p-7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (p+3)(p-7)=0 equation:


Simplifying
(p + 3)(p + -7) = 0

Reorder the terms:
(3 + p)(p + -7) = 0

Reorder the terms:
(3 + p)(-7 + p) = 0

Multiply (3 + p) * (-7 + p)
(3(-7 + p) + p(-7 + p)) = 0
((-7 * 3 + p * 3) + p(-7 + p)) = 0
((-21 + 3p) + p(-7 + p)) = 0
(-21 + 3p + (-7 * p + p * p)) = 0
(-21 + 3p + (-7p + p2)) = 0

Combine like terms: 3p + -7p = -4p
(-21 + -4p + p2) = 0

Solving
-21 + -4p + p2 = 0

Solving for variable 'p'.

Factor a trinomial.
(-3 + -1p)(7 + -1p) = 0

Subproblem 1

Set the factor '(-3 + -1p)' equal to zero and attempt to solve: Simplifying -3 + -1p = 0 Solving -3 + -1p = 0 Move all terms containing p to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1p = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1p = 0 + 3 -1p = 0 + 3 Combine like terms: 0 + 3 = 3 -1p = 3 Divide each side by '-1'. p = -3 Simplifying p = -3

Subproblem 2

Set the factor '(7 + -1p)' equal to zero and attempt to solve: Simplifying 7 + -1p = 0 Solving 7 + -1p = 0 Move all terms containing p to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1p = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1p = 0 + -7 -1p = 0 + -7 Combine like terms: 0 + -7 = -7 -1p = -7 Divide each side by '-1'. p = 7 Simplifying p = 7

Solution

p = {-3, 7}

See similar equations:

| 11+2x=19X | | -16+16t=17t | | 10(r+10)=6(-7-2)-4r | | tan58=6/x | | 9+2(2x+1)=1 | | 5+2k=3 | | 12/3=n | | x^6-2x=0 | | 9u^-4/9u^8 | | 27(p/3)*5(3p).6(2p).4(p) | | 10(r-2)=-5r | | 2u-16=4u-2 | | ln(5x+1)=4 | | z^2+9z=-25 | | 15E+6E=84 | | n/36=1/4 | | 2y=3(4-y) | | -x^2+12x=-19 | | 0.375z+2.25=0.8z-2.4 | | (4x-5)(x-7)=0 | | Sqrt(-x)=-1 | | 5/12=n/6- | | 3/27=9/n | | Ex+x=E | | (3x-5)=ln*306 | | 3x-5=5x+35 | | n/5=24/10 | | 2x+50=2+6x | | G(x)=1.1-ln(2x+5) | | -2x=-x^2-5x+12 | | -7+-18y+18=30y+20+3 | | 5x+y=163 |

Equations solver categories